Congregational culture and identity politics in a lesbian, gay, bisexual, and transgender synagogue: making inclusiveness and religious practice one and the same - Norman, Jon R. (The journal of religion & society, 2011)
This article uses ethnographic fieldwork to investigate the intersection of American liberal values with traditional religious ideals. Members of a gay, lesbian, bisexual, and transgender synagogue develop a local congregational culture that integrates identity politics into Judaism as a way of counteracting their exclusion from both religious and secular institutions in American society. Congregants reformulate their practice of Judaism to accommodate liberal ideals in ways sometimes contradictory to both sets of beliefs; these contradictions, although perhaps detrimental to the maintenance of traditional forms of Judaism, are a reasonable and necessary congregational response to contemporary attitudes among Jews in the United States in the early 21st century that emphasize disaffiliation with organized religion.